Aluminium-based metal-organic framework-fabricated electrochemical sensor for ultrasensitive hydroquinone hazard detection in water samples - Sim, Siew Ming (2020)
A sensitive electrochemical sensor based on aluminium-based metal-organic framework (CAU-1) deposited glassy carbon electrode (GCE) was utilized to detect hydroquinone (HQ), an environmental pollutant in the water sample. The synthesized CAU-1 was characterized by Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDS). The FT-IR results revealed the C=O vibrations presented in the as-synthesized CAU-1 sample which proved the incorporation of the amino-terephthalic acid in CAU-1. Besides, since the XRD pattern obtained for the as-synthesized CAU-1 sample was in good agreement with the simulated CAU-1 (CCDC: 723320), this strongly proved the successful synthesized of the CAU-1. Furthermore, CAU-1 showed rod-shaped morphology with an average length of 280 ± 33 nm through SEM analysis. Besides, CAU-1 had a Langmuir surface area of 1349 m2g-1 and a micropore volume of 0.41 cm3 g-1. The CAU-1 was successfully fabricated on GCE using nafion as a immobilization matrix. The electrochemical behavior of the CAU-1/GCE was studied by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) analysis. The EIS result proved that the modified CAU-1/GCE had lower resistance, which is 683 Ω compared to bare GCE. This indicated that CAU-1 with high porosity and high surface area had contributed to the fast electron transfer between electrode-electrolyte interface. The electrochemical behavior of HQ was investigated at CAU-1/GCE surface and studied the kinetics of HQ oxidation. The CAU-1 fabricated electrode highly catalyzed the oxidation of HQ than the bare GCE. The CAU-1/GCE was proven to have excellent repeatability with relative standard deviation (RSD) of 0.69% for the same sensor that runs 20 cycles consecutively and RSD of 3.96% for four sensors reproduced by using the same procedure. Besides, this sensor also shows good selectivity and anti-interference properties in HQ detection with the detection limit of 0.015 μM with an excellent sensitivity of 1555.7 μA/mM/cm2. Furthermore, the recovery of HQ was 99.34 % to 103.93 % which proved the practical applicability and reliability of the modified CAU-1/GCE in the real-life application.